2014
DOI: 10.1039/c4cy01018c
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis of pyrroles via acceptorless dehydrogenative condensation of secondary alcohols and 1,2-amino alcohols mediated by a robust and reusable catalyst based on nanometer-sized iridium particles

Abstract: The synthesis of pyrroles via acceptorless dehydrogenative condensation of secondary alcohols and 1,2-amino alcohols mediated by a robust and reusable catalyst based on nanometer-sized iridium particles †

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 89 publications
(67 citation statements)
references
References 76 publications
0
61
1
4
Order By: Relevance
“…(1), the reactions with 0.03 mol% of Pt/C for 96 h resulted in 83% yield, corresponding to TON of 2767. This TON is larger than those for previous homogeneous Ir (TON=1860) 4 and Ru (TON=150) 6 catalysts and a heterogeneous Ir catalyst (TON=260) 8 for the same reaction. Table 3 demonstrates substrate scope of the dehydrogenative synthesis of 2,5-disubstituted pyrroles from 1,2-amino alcohols (1) and 1.5 equiv.…”
Section: Resultsmentioning
confidence: 49%
See 4 more Smart Citations
“…(1), the reactions with 0.03 mol% of Pt/C for 96 h resulted in 83% yield, corresponding to TON of 2767. This TON is larger than those for previous homogeneous Ir (TON=1860) 4 and Ru (TON=150) 6 catalysts and a heterogeneous Ir catalyst (TON=260) 8 for the same reaction. Table 3 demonstrates substrate scope of the dehydrogenative synthesis of 2,5-disubstituted pyrroles from 1,2-amino alcohols (1) and 1.5 equiv.…”
Section: Resultsmentioning
confidence: 49%
“…The result shows that diglyme (entry 8) would serve as the best solvent. The reaction with various basic additives (entries 8,[14][15][16][17][18] showed that KOtBu (entry 8) was more effective than other bases such as K 2 CO 3 , Cs 2 CO 3 , NaOH, NaOMe and KOH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations